Academic Anxiety among Reserved & Non-Reserved Category Senior Secondary School Students of Jammu Division (Asian Education Studies, 2016)
Background: Indian society constitutes minorities, schedule castes, schedule tribes, and other backward communities. In order to uplift them through different policies and plans Government of India in consultation with Jammu and Kashmir Government had kept them in reserved (SC, ST, OBC, RBA, ALC) & non-reserved (General/Open) category. Does students belonging to reserved & non-reserved category differ in terms of their academic anxiety has motivated the researcher to approach this problem. Aim: The main objectives of the study were to find out the relationship between academic anxiety, intelligence and study habits of total sample groups and sub-groups. To explore category (reserved & non-reserved) and gender (male & female) differences in academic anxiety, intelligence and study habits of total sample groups and sub-groups and to find out significance of difference in the mean scores of academic anxiety among all comparative groups under study. Method: A sample of 537 students including 329 reserved categories and 208 non-reserved category students aged between 14-18 years were selected through stratified random sampling technique. Data was collected by administering self-constructed Academic Anxiety Scale bearing dependable validity and reliability, Standardised Group Test of Intelligence by Ahuja (2009) and Study Habits Inventory by Lajwanti, Chandel, & Paliwal. (2013). Results: Academic anxiety was correlated with intelligence and study habits of total sample groups and sub-groups under study. On an average students belonging to non-reserved category were higher in academic anxiety scores but were possessing better study habits than reserved categories students. In terms of academic anxiety’s mean score differences among all comparative groups under study, only reserved categories females were suffering more from academic anxiety than reserved categories males sample. Conclusion: More research on psychological health of reserved & non-reserved categories students especially in their socio-cultural and political context is needed so as to evolve effective and practical preventive measures.